Mechanics of material interfaces : proceedings of the technical sessions on mechanics of material interfaces held at the ASCE/ASME Mechanics Conference, Albuquerque, New Mexico, June 23-26, 1985 - Selvadurai, A. P. S.; Voyiadjis, G. Z. (Studies in applied mechanics ;, 1986)
The category of problems which examines the mechanical behaviour of contact regions constitutes an important branch of applied mechanics with extensive engineering applications. The results of such research can be applied to the study of mechanics of composite materials, tribology, soil-foundation interaction, mechanics of rock interfaces, modelling of damage phenomena and micro-mechanics. In classical studies, the modelling of interface responses has focussed on purely idealized forms of interface phenomena which range from frictionless contact to bonded contact, with Coulomb friction or fi.